The association of LPA gene copy number variation and Apolipoprotein E (Apo E) Gene Polymorphism in young acute Myocardial Infarction - Mohd Zamri, Iffah Irdina; Abdullah, Nor Zamzila; A Talib, Noorlelawati; Muhammad Musa, Nurul Ashikin; Abdullah, Aszrin (2022)
Introduction: Acute Myocardial Infarction (AMI) continues to be the principle cause of mortality and morbidity globally. In Malaysia, people are getting AMI at younger age compared to well-developed countries. LPA gene and Apo E genes exert important roles in the regulation of lipid metabolism, which contribute to the pathogenesis of atherosclerosis and thus AMI. However, the association between these two genes in the pathogenesis of AMI have not yet been studied in the young population. Method: This study investigated the copy number variation (CNV) of LPA gene and Apo E gene polymorphism in 20 Young AMI patients and 20 controls. The DNA was extracted from the buffy coat. CNV of LPA gene detection was performed using digital PCR (dPCR) and Apo E was genotyped using multiplex polymerase chain reaction (PCR) based on the dual priming oligonucleotide. Results: There was no significant association between CNV of LPA gene and polymorphism of Apo E gene with Young AMI patients. Although not statistically significant (p=0.459), the gain of copy number was higher in Young AMI patients (25%) compared to healthy controls (10%). The finding also showed that the E3/E3 was the most common genotype in all groups, followed by E3/E4 genotypes. Additionally, ℇ4 allele in Young AMI patients was more frequent, 5(0.125) than ℇ2 allele 3(0.075). Conclusion: Our preliminary result identified a higher copy number of LPA gene and ℇ4 allele in patients with young AMI. This observation requires further evaluation.